Determinación de la incidencia de tres sistemas de labranza mecanizada sobre la disponibilidad de agua para el cultivo de maíz (Zea mayz), en la época seca en la zona de Quevedo. - Burgos Jiménez, Jorge Stalín (2016)
The present research was carried out from July to October 2016, in the dry season, in the experimental farm "La María", property of Quevedo State Technical University, located in the Km, 7 via Quevedo - El Empalme, province of Los Rivers, geographical coordinates 79 º 32` west longitude and 01 º 06` south latitude, with an elevation of 120 meters above sea level. The objective of this study was to determine the incidence of three tillage systems on the availability of water in the soil for maize cultivation and the influence on maize crop productivity. The treatments studied were: conventional tillage, minimum tillage, zero tillage. For the field implementation the treatments were distributed under an experimental design of plots divided into three replicates. Averages were subjected to DMS and Duncan at 95% probability. To test the effect of tillage systems on water availability, maize, Somma and Thunder hybrids were used, in which the percentage of emergence, plant heights at 30, 60 and 90 days, diameter and length of Ear, ear of corn, weight of 100 seeds and yield. From the analysis and interpretation of the results it was concluded that the conventional tillage system improved the soil physical conditions and achieved a higher percentage of emergence and a higher plant height at 30, 60 and 90 days, which led to higher yields for the two Maize genetic materials that were tested instead in diameter, length, number of rows, ear weight, weight of 100 seeds, in the tillage systems did not present significant statistical difference; But the conventional tillage system predominated as the best one in the availability of water in the soil the system of zero tillage presented the greater capacity of retention of water available, maintaining a vegetal cover in its surface that protects to the ground and it avoids the loss Of moisture by evaporation. The phenological period of greatest water requirement was from sowing to flowering ranging from 79.7 to 82.5 mm, surpassing the flowering-ripening period between 6.0 and 10.4 mm and the water requirements were higher in the vegetative stage (internode-to-bloom lengthening) Followed by the reproductive stage (from flowering - to filling of grains). The highest yield was obtained with the conventional tillage system with 5629.6 kg / ha, superior at 5188.5 and 5044.2 kg / ha to the Minimum and Zero tillage systems, respectively. KEYWORDS: Tillage systems, Hybrid, maize, zero tillage.